Monotonic and Cyclic Seismic Analyses of Old-Type RC Columns with Short Lap Splices - Konstantinos G. Megalooikonomou (Construction Materials, 2024)
Reinforced concrete (RC) columns with short lap splices built in the early 1970s or before are known to have deficient seismic strength and ductility. These short lap splices are poorly confined and located right above the foundation level, where it is known that the inelastic demands are high under seismic loading. In this study, a numerical model for estimating the lateral strength and deformation of RC columns with short lap splices is introduced. The latter model is based on local bond–slip analytical models derived from isolated anchored bars through the closed-form solution of the differential equation of bond. The proposed model is correlated to experimental data from cyclic loading tests on RC columns with deficient lap splices. It can be seen that the strength of short lap splices, the failure mode, and the column’s lateral resistance and deformation are in good agreement with the experimental results both under monotonic and cyclic seismic analyses.